Chemical cleaning of potable water membranes: A review - Porcelli, Nicandro; Judd, Simon J. (Elsevier Science B.V., Amsterdam., 2010)
The literature on chemical cleaning of polymeric hollow fibre ultrafiltration and microfiltration membranes used in the filtration of water for municipal water supply is reviewed. The review considers the chemical cleaning mechanism, and the perceived link between this and membrane fouling by natural organic matter (NOM)—the principal foulant in municipal potable water applications. Existing chemical cleaning agents used for this duty are considered individually and their cleaning action described, along with the most commonly applied cleaning protocols (i.e. the cleaning conditions, cleaning sequence and method of cleaning agent application). It is concluded that chemical cleaning is poorly understood and not extensively investigated, in marked contrast to the much more widely studied area of membrane fouling generally, for which there are thousands of published studies. Studies of chemical cleaning specifically have instead been generally limited either to qualitative measurements, such as the use of surface or other analytical tools to characterise membrane foulants and record their removal, or incidental permeability recovery recorded from cleaning events during pilot or full-scale trials. It is proposed that a chemical cleaning index is needed, analogous to the recently proposed general membrane fouling index, based on empirical data to inform cleaning protocols for specific duties and feedwater qualit
Keywords: Chemical cleaning; Microfiltration; Ultrafiltration; Potable water